Synergistic Effect of Azotobacter nigricans and Nitrogen Phosphorus Potassium Fertilizer on Agronomic and Yieldtraits of Maize (Zea mays L.) - Sagar, Alka; Sayyed, R. Z.; Ramteke, Pramod W.; Ramakrishna, Wusirika; Poczai, Peter; Al Obaid, Sami; Ansari, Mohammad Javed (Frontiers in Plant Science, 2022)
Plant growth-promoting bacteria (PGPB) Azotobacter spp. is the most promising bacteria among all microorganisms. It is an aerobic, free-living, and N2-fixing bacterium that commonly lives in soil, water, and sediments. It can be used as a biofertilizer for plant growth and nutrient utilization efficiency. Maize is the highly consumed cereal food crop of the cosmopolitan population, and the sustainable maize productivity achieved by applying bacteria in combination with nitrogen phosphorus potassium (NPK) is promising. In the present study, a bacterial isolate (PR19). Azotobacter nigricans, obtained from the soil of an organic farm was evaluated for its plant growth promoting potential alone and in combination with an inorganic fertilizer (NPK) included. The bacterial cultue (PR19) was screened for its morphological, biochemical, and plant growth-promoting characteristics, sequenced by the 16S rDNA method, and submitted to NCBI for the confirmation of strain identification. Further, the inoculation effect of the bacterial culture (PR19) in combination with NPK on growth and yield parameters of maize under pot were analyzed. Based on phenotypic and molecular characteristics, PR19 was identified as Azotobacter nigricans it was submitted to NCBI genbank under the accession No. KP966496. The bacterial isolate possessed multiple plant growth-promoting (MPGP) traits such as the production of ammonia, siderophore, indole-3-acetic acid (IAA), and ACC Deaminase (ACCD). It showed phosphate solubilization activity and tolerance to 20% salt, wide range of pH 5–9, higher levels of trace elements and heavy metals, and resistance to multiple antibiotics. PR19 expressed significantly increased (p < 0.001) antioxidant enzyme activities (SOD, CAT, and GSH) under the abiotic stress of salinity and pH. In vitro condition, inoculation of maize with the PR19 showed a significant increase in seed germination and enhancement in elongation of root and shoot compared to untreated control. The combined application of the PR19 and NPK treatments showed similar significant results in all growth and yield parameters of maize variety SHIATS-M S2. This study is the first report on the beneficial effects of organic farm isolated PR19-NPK treatment combinations on sustainable maize productivity.